Quantification of aflatoxin M1 carry-over rate from feed to soft cheese - D. Costamagna; M. Gaggiotti; C.A. Chiericatti; L. Costabel; G.M.L. Audero; M. Taverna; M.L. Signorini (Toxicology Reports, 2019)
From January to December 2016, samples of milk and feeds of dairy cattle were monthly collected. The concentration of mycotoxins in all matrices was determined using the enzymatic immunoassay technique. The average concentration of aflatoxin B1 (AFB1), deoxynivalenol (DON) and zearalenone (ZEA) in feed was 3.01, 218.5 and 467 ug/kg, respectively. The average AFB1 carry-over rate was 0.84% with a variation between 0.05 to 5.93%. Particle size of the feed (P = 0.030) and individual milk production (P = 0.001) affected this rate. Mini-soft cheeses were produced using milk naturally contaminated with aflatoxin M1 (AFM1) as raw material to study its distribution both in whey and in cheese. The average level of AFM1 in milk was 0.014 μg/l. None of milk samples exceeded the maximum level accepted for AFB1 by the Southern Common Market (MERCOSUR) legislation (0.5 μg/l) and only 5.5% of samples exceeded the European Union (UE) regulations (0.05 μg/l). After the cheese elaboration, the concentration of AFM1 was determined in whey and in cheese. The greatest proportion (60%) was detected in whey while 40% AFM1 remained in the cheese. However, the concentration of AFM1 was higher in the cheese compared to the original milk. Keywords: Aflatoxin B1, Aflatoxin M1, Carry-over, Cheese